The effect of using the Aero Pilates device in rehabilitating the connective muscle injury (groinal exclusion) in a handball student (Global Scientific Review, 2024)
The research aims to prepare a rehabilitation program using the Pilates device to rehabilitate the groin injury in handball players. The researchers used the experimental approach to suit the nature of solving the problem. The research sample represented Dhi Qar Governorate players who suffer from a connective muscle injury in handball. The research sample amounted to (6) players. Injured patients, the researchers conducted homogeneity in the research variables. The rehabilitation units were applied by the researchers. The duration of the rehabilitation program was (8) weeks from 5/17/2023 until 7/9/2023 at a rate of three rehabilitation units per week. The researchers concluded that the device Pilates helped players rehabilitate connective muscle injuries.